2015
DOI: 10.1002/mdc3.12232
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features in Border Terrier Dogs with Paroxysmal Involuntary Movements

Abstract: 42Funding sources for the study: none. 44 Abstract 45Background -There have been anecdotal reports of episodic involuntary movements in the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
15
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 17 publications
3
15
2
Order By: Relevance
“…PxDs have been described in other canine breeds . In the majority of breeds with PxD affecting the limbs and trunk, the first episode of PxD is observed in the first year after birth .…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…PxDs have been described in other canine breeds . In the majority of breeds with PxD affecting the limbs and trunk, the first episode of PxD is observed in the first year after birth .…”
Section: Discussionsupporting
confidence: 87%
“…In the majority of breeds with PxD affecting the limbs and trunk, the first episode of PxD is observed in the first year after birth . However, in the NT dogs in this study, the median and mean age at the first observed episode of PxD was 3 years, similar to what has been reported in the border terrier . Other similarities with the border terrier PxD include no gender predilection in affected dogs; seeking to be near the owner at the start of an episode; certain aspects of the episode phenomenology, such as the sustained hypertonicity of the appendicular and lumbar muscles, repeated licking movements, and side‐to‐side swaying movements of the body; and episode frequency .…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations